"If it benefits someone, it will be good:" perspectives on research participation from pregnant women living with HIV. Issue 3 (4th March 2023) - Raciti, Catherine G.; Marsha, Joy; Nafiseh, Amira A.; Masese, Eric R.; Apondi, Edith; McHenry, Megan S.
ABSTRACT: Pregnant women living with HIV (PWLHIV) are becoming increasingly involved in HIV research; however, the ethical concerns regarding their decision-making related to research participation are understudied. This qualitative study aimed to understand the perspectives and lived research experiences of PWLHIV, intending to identify important considerations to inform best practices. This study used semi-structured interviews (SSIs) of PWLHIV who participated in research studies in Eldoret, Kenya. All interviews were audio-recorded, transcribed, and translated. Qualitative analyses were performed, with line-by-line coding, constant comparison, axial coding, and triangulation to identify central concepts. Twelve PWLHIV participated. Overall, participants had positive experiences with HIV research. Most participants had difficulty distinguishing the differences between the research process and enhanced clinical care. They reported a willingness to participate in future HIV research studies and indicated altruism as the primary motivator. Participants identified their preferences and experiences with recruitment, consenting, reimbursement, and enrolment of infants in HIV research. The largest barrier for participating in HIV research was identified as a concern that participation would lead to HIV disclosure. By understanding the lived experiences of PWLHIV who participate in HIV research, future researchers can design studies and consenting processes to optimize ethical research practices.